Enhancements To The FHWA Deep Foundation Load Test Database - Carl D. Ealy (Deep Foundations Institute, 2002)
Work is being done to web enable the FHWA Deep foundation Load Test Database. Originally designed to function in the client server environment via modem, access to the database both for data maintenance and user queries has been upgraded to take advantage of the Internet and current and future information technology innovations. The DFLTD will be part of an Automated Geotechnical Information and Design Aid System, the object of which is to assist those involved with managing and maintaining our nation's highway infrastructure. The system will also meet the needs of university and other research institutions for a statistically meaningful source of high quality data for the development and verification of improved analysis methods, in-situ testing methods, etc.